2017
DOI: 10.1515/subboec-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Campus Service Quality Recreational Scale

Abstract: Abstract:In the past two decades, several researchers have applied service quality frameworks in sport-related domains in measuring service quality among participants. However, university campus recreation has been scarce as compared to organised sport at local, regional and national levels, which often depends on a limited tenure linked to their membership as a registered student at a university. The purpose of the study is to investigate service quality dimensions as perceived by university leisure and recre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The results of this study also reveal that participant benefits and service quality explained 53% of the variance in program satisfaction and 22% of the variance in student retention, with social learning outcomes, service quality, and emotional wellness serving as unique predictors in the former, and physical health and wellness serving as the only unique predictor in the latter. With regards to the particular impact of social learning outcomes and service quality on program satisfaction, the results appear to align with previous research that points to the importance of well-designed programming (e.g., Gallardo et al, 2009;Ko & Pastore, 2005), the social aspects of campus recreation (e.g., Lower-Hoppe et al, 2020;Mokoena & Dhurup, 2017), and contributions to student emotional wellness (Lewis et al, 2002) in determining one's satisfaction with their participation experience. Providing satisfactory experiences for intramural sport participants has been found to influence future participation (Brady & Robertson, 2001;Osman et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study also reveal that participant benefits and service quality explained 53% of the variance in program satisfaction and 22% of the variance in student retention, with social learning outcomes, service quality, and emotional wellness serving as unique predictors in the former, and physical health and wellness serving as the only unique predictor in the latter. With regards to the particular impact of social learning outcomes and service quality on program satisfaction, the results appear to align with previous research that points to the importance of well-designed programming (e.g., Gallardo et al, 2009;Ko & Pastore, 2005), the social aspects of campus recreation (e.g., Lower-Hoppe et al, 2020;Mokoena & Dhurup, 2017), and contributions to student emotional wellness (Lewis et al, 2002) in determining one's satisfaction with their participation experience. Providing satisfactory experiences for intramural sport participants has been found to influence future participation (Brady & Robertson, 2001;Osman et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Scholars have focused largely on aspects of the physical environment as key factors influencing perceptions of service quality, including characteristics of sport facilities such as proximity (Deelen et al, 2016;Wicker et al, 2013), aesthetics (Gallardo et al, 2009), and availability of fitness equipment (Makubuya et al, 2020). Further, previous research has pointed to programmatic factors that have influenced perceptions of service quality, including the types of programs offered (Hallmann et al, 2012) and opportunities to socialize (Mokoena & Dhurup, 2017). Evidently, participants in recreational sports, including intramural sport, have broad expectations and perceptions of service quality that relate to facility infrastructure, programming decisions, and the interpersonal nature of recreational sports.…”
Section: Recreational Sport Service Qualitymentioning
confidence: 99%
“…The recreational and sports facilities available on campus offer the students an opportunity to participate in activities that can keep them fit or some other form of activities that they may prefer (Mokoena & Dhurup, 2017). These facilities play an essential role in students' overall satisfaction with the higher educational institute experience and the campus life experience (Schmidt et al, 2017), which is why higher education institutions today are striving to increase recreational and sports activities for the students.…”
Section: Student Services and University Environmentmentioning
confidence: 99%
“…Existing literature suggests that students' welfare services have received varied attention from higher education service providers (International Students Survey, 2021;Mokoena & Dhurup, 2017;Sohail & Hasan, 2020). In Australia, a continent which over the years has maintained a reputation as a destination for quality higher education, International Students Survey (2021) found that 71.0% of the students were satisfied with the quality of students' welfare services in the universities.…”
Section: Introductionmentioning
confidence: 99%